2022
DOI: 10.3389/fmed.2021.582403
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width in Hospitalized COVID-19 Patients

Abstract: Introduction: Coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is causing dramatic morbidity and mortality worldwide. The Red Blood Cell Distribution Width (RDW) has been strongly associated with increased morbidity and mortality in multiple diseases.Objective: To assess if elevated RDW is associated with unfavorable outcomes in hospitalized COVID-19.Methods: We retrospectively studied clinical outcomes of hospitalized COVID-19 patients for their RDW … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…The extracted probabilistic relationships inform evidence-based knowledge on the course of COVID-19 pneumonia with inpatient treatment. Some of these relationships matched with the results of other researchers [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. However, other extracted results are new, such as the influence of monocytes from the third time interval (10–17 days) to lethality.…”
Section: Discussionsupporting
confidence: 87%
“…The extracted probabilistic relationships inform evidence-based knowledge on the course of COVID-19 pneumonia with inpatient treatment. Some of these relationships matched with the results of other researchers [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. However, other extracted results are new, such as the influence of monocytes from the third time interval (10–17 days) to lethality.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, RDW increased at the end of the study period, indicating a more diverse RBC population. Altered RDW in COVID-19 was already observed by other groups, associating elevated RDW with all-cause mortality [ 37 ] and RDW during hospitalization with a significantly increased risk of mortality and septic shock [ 8 , 38 ]. An increased RBC turnover rate by SARS-CoV-2 with accelerated lysis of old RBCs and synthesis of new cells would explain the observed reversed hemorheological alterations at T30 when the initially affected cells are gradually replaced.…”
Section: Discussionmentioning
confidence: 80%
“…In recent years, a number of diagnostic and prognostic markers, both alone and in combination, have been tested on individuals diagnosed with AP [16][17][18]. After elevated RDW was established as a predictor of poor outcomes in chronic heart failure in 2007, multiple studies have shown that it is signifcantly related to short-term mortality outcomes in a range of infammatory disorders [19,20]. Additionally, Jin [21] and Zhang's [22] studies demonstrated a strong correlation between RDW and acute pancreatitis mortality.…”
Section: Discussionmentioning
confidence: 99%